CREDIT RISK COMPLIANCE LEVELS AND TECHNICAL EFFICIENCY OF COMMERCIAL BANKS IN KENYA: A DATA ENVELOPMENT ANALYSIS (DEA) MODEL APPROACH - Stephen Kisuli; Tabitha Nasieku; Gordon Opuodho; Kimanzi Kalundu (ZILLZELL MEDIA PRIMA, 2026)
This paper investigates how level of compliance with credit risk regulatory guidelines issued by the central bank of Kenya impacts on technical efficiency whilst considering bank size as a moderating variable. The study adopts a quantitative research design, where a panel data of ten years of a sample of all the licensed commercial banks in Kenya is applied. The technical efficiency scores are estimated with the help of Data Envelopment Analysis (DEA) and the correlation between compliance with credit risk and technical efficiency is estimated with the help of the two-limit Tobit regression model estimated by the means of the Maximum Likelihood Estimation (MLE) method. The study findings established that there is a negative and statistically significant correlation between credit risk and technical efficiency meaning that an increase in credit risk correlates with decreased technical efficiency among commercial banks. Bank size was found to be statistically significant in determining the impact of technical efficiency, which points to the role of scale-related variables in efficiency performance. The study suggests commercial banks to improve their credit risk management and the level of compliance with prudential credit risk guidelines to minimize excessive credit risk exposure and to promote technical efficiency. Moreover, regulators and policymakers are advised to take into account bank size in designing and implementing credit risk regulatory frameworks. The paper also recommends that future research should generalize the study to other financial institutions, including microfinance institutions and cooperative banks, and use longer time horizons to reflect changing regulatory and efficiency dynamics of the financial sector.